Victims or Heroes?—Disability Representations in a Hungarian Online News Media Portal - Carmen Svastics; Gabor Petri; Agnes Kozma; Anikó Bernát (Disabilities)
While studies consistently show that the popular media often provide medicalized images of disabled people as “other” or inferior, dynamic societal changes, such as the diffusion of human rights laws, increasing public awareness, and the mediatization of disability activism, also influence media representations. The present research aims to identify relevant discursive practices in Hungarian online news media, a non-Western European country with about 50 years of a state party system under communism, and offer insight into how progressive policy changes and mediatized activism shape media features on disability. To establish the dataset, the most visited and independent online news media portal in Hungary (24.hu) was searched for articles discussing disability between 2019 and 2022. The 481 relevant articles extracted were analyzed using Critical Discourse Analysis (CDA) with the help of MAXQDA 2020. The findings reveal a multiplicity of disability representations: medicalized and victimized images on the one hand, and reports of resilience and “heroism” on the other. Three distinct discursive practices are identified: (1) traditional/ableist representations, (2) alternative representations with ableist framing, and (3) agency and the co-creation of disability representations. Results suggest that even 30 years after the political changes, disabled people’s collective agency is marginal in Hungary, and that socio-legal changes and mediatized disability activism are yet to influence news media features.